Psychopathological and neuropsychological disorders associated with chronic primary visceral pain: Systematic review - Arévalo-Martínez, Alejandro; Moreno-Manso, Juan Manuel; García-Baamonde, María Elena; Blázquez-Alonso, Macarena; Cantillo-Cordero, Pilar (Frontiers in Psychology, 2022)
The World Health Organization (WHO), in its last review of its International Classification of Diseases, established a new classification for chronic pain. Among the principal categories, of particular interest is chronic primary pain as a new type of diagnosis in those cases in which the aetiology of the disease is not clear, being termed as chronic primary visceral pain when it is situated in the thorax, abdomen, or pelvis. Due to the novelty of the term, the objective of this systematic review is to examine the current deficits at a psychopathological and neuropsychological level as far as chronic primary visceral pain is concerned. We carried out a search of the scientific literature following the PRISMA directives using the Pubmed, Medline, PsycInfo and Scopus databases. A total of 33 articles were selected after applying the inclusion and exclusion criteria. The analysis of the studies shows that persons with chronic primary visceral pain suffer from at least one psychological disorder; the most prevalent being anxiety, depressive or somatoform disorders. The most frequent psychopathological symptoms are anxiety, depression, and somatization. Similarly, the findings are insufficient to determine the existence of deficits in the domains of executive functioning, memory and intelligence. However, the existence of attention biases does seem to be clear. This review supposes a starting point for conceptualising chronic primary visceral pain. It is necessary to continue further research to obtain a better understanding of this pathology and its associated deficits.